TEACHING MATERIALS MODEL FOLKLORE IN LEARNING INDONESIAN BASED ON THEMATIK APPROACH - Satinem, S; HP, Achmad (INTERNATIONAL JOURNAL OF LANGUAGE EDUCATION AND CULTURE REVIEW, 2015)
Literature module in this research is regional literature module which is developed based on the previous module in teaching and learning Indonesia The aim of this research is to produce a model of module for Indonesia based on the thematic approach from folklore for the third grade students of elementary school in Lubuklinggau, In this research, further development was done based on teacher and studentsâ need analysis. Research and Development (R&D) method is used in this research. This research combined research model of Brog& Gall and development model of Dick & Carey. Therefore, research and development is a process of developing and validating educational product. Educational product in this research refers to the syllabus, module, and lesson plan/instructional design. Based on the data gathered from the application of developmental plan of learning model which consist of syllabus, lesson plan, limited try out test, large try out test, model effectiveness test, and module readability test, it can be stated that the teaching and learning model which is developed can increase the third grade studentsâ achievement at elementary school in Indonesian teaching and learning with the source of regional literature.